Helical CT angiography of fenestrated stent grafting of abdominal aortic aneurysms - Sun, Zhonghua (University of Malaya, 2009)
Fenestrated stent grafts have been developed to treat patients with abdominal aortic aneurysms (AAA) associated with complicated aneurysm necks, such as short necks, severe angulated or poor quality necks (presence of calcification or thrombus). The technique is performed by creating an opening in the graft material so that the stent graft can be placed above the renal and other visceral branches without compromising blood perfusion to these vessels. In most situations, a supporting stent is inserted into the fenestrated vessel to provide fixation of the fenestrated vessel against stent grafts, as well as preserve patency of the vessel. Helical CT angiography (CTA) is the preferred imaging modality in both pre-operative planning and post-procedural follow-up of fenestrated repair of AAA. The main concerns of fenestrated stent grafting lie in the following two aspects: patency of the fenestrated vessels and position of the fenestrated stents in relation to the artery branches. In this article, we present the clinical applications of 2D and 3D visualizations in the follow-up of patients with AAA treated with fenestrated stent grafts, with aim of providing useful information to readers and increasing their knowledge of an increasingly used technique, fenestrated stent grafting in the treatment of AAA.